PARTISIPASI SUAMI DALAM KUNJUNGAN ANTENATAL CARE DI INDONESIA: SYSTEMATIC REVIEW - Alwi, M. Akbar; Hamzah, Hadzmawaty; Ningsih, Nining Ade; Mahfudah, Ulfah (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2024)
Maternal Mortality Rate is an indicator of public health status. Maternal death can be prevented by maximizing antenatal care (ANC) visits.Participation of husband is very important to assist pregnant women access ANC. The aim of this study was to determine the factors that influence husbands' involvement in antenatal care visits. This research is a systematic review by searching literaturs on Google Scholar based on the purpose of this research. The articles selected in this research are articles published in 2015-2023. The resuls of this study revealed that husband and wife's age, husband and wife's education, husband and wife's occupation, income, knowledge, pregnancy status, area of residence, social status/wealth, and parity are factors that influence husbands' participation in ANC visits. Based on the results of this research, it is necessary to provide information to husbands regarding the benefits of ANC and the importance of carrying out ANC as an effort to prevent maternal death.